Development of a family empowerment model to enhance the parental monitoring of child development and reduce stunting through filial values - Utami, Sri; Susilaningrum, Rekawati; Yunita, Evi; Nursalam, Nursalam (Universitas Airlangga, 2025)
Introduction: The monitoring of child development by parents plays an important role in reducing the incidence of stunting. This research aimed to develop a family empowerment model regarding the ability to monitor child development through the role of filial value. Methods: The research design used was an explanatory survey method. The study population was all families with children living in the working area of the Health Center in Surabaya. Sampling was carried out using simple random sampling of 275 families from April to September 2024. A questionnaire was used and the secondary data was related to the nutritional status of toddlers. The data analysis involved the use of the smart PLS (Partial Least Squares) statistical test with a significance level of T > 1.96. Results: Core values have a big impact on the commitment to monitoring toddler development (t = 14.375). Core values cannot directly influence monitoring toddler development (t = .664; P-value= .507) but must go through commitment (t = 2.521; P-value = .012) and empowerment (t = 3.781; P-value= < .001). Conclusion: The role of filial value through commitment can shape family empowerment regarding the ability to monitor the development of children. These findings can be applied to families with children to accelerate the reduction in stunting rates. Further research is needed regarding the implementation of this model. Keywords: children; empowerment; family; filial value; monitoring ability; stunting